Oxidation and volatilisation behaviour of a type 430 stainless steel coated by Mn-Co oxide by slurry method with pre-oxidation for SOFC interconnect application - Chandra-ambhorn, Somrerk; Homjabok, Wanna; Chandra-ambhorn, Walairat; Thublaor, Thammaporn; Siripongsakul, Thamrongsin (My University, 2021)
An AISI 430 stainless steel was coated by Mn-Co spinel using a slurry method. Pre-oxidation before the coating helped reduce the oxidation rate of the coated steel at 800 °C in O2-5%H2O, relating to the formation of the continuous chromia layer which inhibited the outward diffusion of iron to the coating layer. It also helped reduce the mass flux of Cr loss due to the volatilisation. The combined molecular and Knudsen diffusion of the volatile species through the coating layer was suggested to explain the reduced volatilisation rate of the coated sample with pre-oxidation.
Keywords: Interconnect; Knudsen diffusion; Oxidation; Solid oxide fuel cells; Stainless steel; Volatilisation